Quantitative Mass Spectrometry-Based Proteomic Profiling for Precision Medicine in Prostate Cancer - Flores-Morales, Amilcar; Iglesias-Gato, Diego (Frontiers in Oncology, 2017)
Prostate cancer is one of the most frequently diagnosed cancer among men in the western societies. Many prostate cancer patients bear tumors that will not threat their lives if left untreated or if treatment is delayed. Our inability for early identification of these patients has resulted in massive overtreatment. Therefore, there is a great need of finding biomarkers for patient stratification according to prognostic risk; as well as there is a need for novel targets that can allow the development of effective treatments for patients that progress to castration-resistant prostate cancer. Most biomarkers in cancer are proteins, including the widely-used Prostate Specific Antigen (PSA). Recent developments in mass spectrometry allow the identification and quantification of thousands of proteins and posttranslational modifications (PTM) from small amounts of biological material, including formalin-fixed paraffin-embedded tissues and biological fluids. Novel diagnostic and prognostic biomarkers have been identified in tissue, blood, urine and seminal plasma of prostate cancer patients, and new insights in the ethology and progression of this disease have been achieved using this technology. In this review, we summarize these findings and discuss the potential of this technology to pave the way towards the clinical implementation of precision medicine in prostate cancer.